A FAKTOR-FAKTOR YANG MEMPENGARUHI LAMANYA PEMBERIAN ASI PADA BADUTA DI DI YOGYAKARTA - Tjekden, Fredy (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Background : The duration of breastfeeding is an illustration of the amount of nutrition and the high immunity of children against various diseases. Methods : In this study, quantitative research methods were using data from the March 2020 National Socio-Economic Survey (Susenas) in the Province of the Special Region of Yogyakarta. Results : Most of the baduta who became the object of the study were still breastfeeding by 82.75 percent and male by 55.85 percent, while for the mother most of them had high school education and above by 80.76 percent, 51.84 percent did not work, lived in urban areas by 76.95 percent, aged 22 - 37 years by 84.30 percent, and most of the nuclear family households by 56.06 percent and including non-poor households by 85.21 percent. Conclusion : The results showed that the variables that influenced the duration of breastfeeding for children under two were mother's education, mother's employment status, area of residence, mother's age, child's gender, family type, expenditure per capita per month.